The Role of Strengthening Exercises in Managing Osteoporotic Spine in Postmenopausal Women: A Comprehensive Review - Liyana, S Abraham; Jeffery, Samuel R (INTI International University, 2025)
Osteoporosis is a chronic disease that occurs in postmenopausal women characterized by low bone mineral density (BMD) and elevated spinal fracture risk. Resistance exercise is routinely advised, but the best protocols are still under research. A literature review from 2017 through 2025 was performed. Twelve trials were selected, comparing the impact of resistance training on spinal BMD and spinal fracture risk in postmenopausal women. Supervised moderate- to high-intensity resistance training improved BMD as much as 6–9% and functional mobility 10–15%. High-impact training produced extra lumbar spine gains in BMD and adding exercise to drugs like zoledronate improved results further. Supervised long-term programs were superior to short-term or home-based programs. Resistance exercise is an important part of osteoporosis treatment in postmenopausal women. More research is needed to optimize exercise prescriptions for long-term bone health.